Effects of Converting Used Paper into Flower Vase on Grade 12 ABM Strand Students in Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
This research focused on the effect of converting used paper into a flower vase. The study revealed that used paper can be made into a helpful product such as a flower vase. A qualitative method was used in this study using the descriptive research design. This study involved 50 selected grade 12 Accountancy, Business, and Management Strandstudents. Converting used paper into a flower vase can reduce the amount of paper waste in every classroom and recycle paper into a new product. Another aspect revealed that the paper flower vase can be used to grow plants instead of manufactured vases. The study revealed that converting used paper into a flower vase can help not only the school but also the environment. The study also showed that the students could plant more trees and flowers by using paper flower vases. The students can also have a pleasant room decorated with paper flower vases.
Keywords: paper waste